MOTIVASI MAHASISWA BERWIRAUSAHA SELAMA BERKULIAH - L Tarigan, Nerys Lourensius; Priana Sukmawaty, Wahyu Eka (Akademi Kesejahteraan Sosial AKK Yogyakarta, 2024)
Student motivation to be entrepreneurial during college is one of the important indicators in building an independent and innovative young generation. This study aims to analyze the level of motivation of students in entrepreneurship, the factors that affect it, and the obstacles faced. This study uses a quantitative approach with a survey method of 300 students from STIE IEU and the AKS-AKK Fashion Design Study Program. Data were collected through a questionnaire based on the Likert scale and analyzed using descriptive statistics and linear regression. The results of the study showed that the average student motivation score for entrepreneurship was 3.8 on the Likert scale of 1-5, which was relatively high. The entrepreneurship education factor had the most significant positive influence on entrepreneurial motivation with a regression coefficient of 0.45, followed by family support with a regression coefficient of 0.36. However, the main obstacles that prevent students from starting a business are limited capital (75%) and concerns about market uncertainty and business risks (62%).